Polar Tourism: Inuit Cultural Heritage in Tourism-Driven Documentaries - Sasso, E. (Comares, 2024)
This essay takes as its starting point such a conceptual metaphor as «Polar Tourism is Cultural and Linguistic Preservation» as exempli!ed by a series of documentaries on Inuit art and Tourism in order to advance a new reading of Inuit art and naming, one which sees them as cognitive practices. Exceptional wildlife sightings, stunning displays of nature, and rare experiences carefully designed to reveal remote cultures in the most authentic and engaging manner are the de!ning aspects of polar tourism as envisioned in «Crystal Serenity Northwest Passage 2017» and «Eskimo Artist: Kenojuak» (1964). I intend to track through these references and look at the issues —the role of documentaries in the spreading of Inuit names, naming strategies for inducing tourism etc.— which they raise. But my central purpose will be to re-read Inuit documentaries from a cognitive perspective. I will analyse the cognitive map of Nunavut with its place names as a country unprepared to welcome millions of tourists. Inuit documentaries acquire a dangerous valence in fostering mass tourism through the lure of Inuit art which could end in ecological disaster.